Factors Affecting Nonprescription Drugs Purchase Decision: The Mediating Role of Patients’ Perception - Ali, Basma Kamal Selim; Gharabawy, Alaa eddin H.; Sergios, Antwan Iskander (The Arab Journal of Administration, 2025)
The current study aimed to explore the factors that influence patients’ purchase decision of non prescription drugs taking into consideration the mediating role of patients’ perception of these drugs. These factors are marketing factors, which include advertising, pharmacists’s recommendations, and the opinion of family and friends, as well as the demographic factors, which include age, gender, income education ,and employment status, sand finally personal factors, which include past personal experiences and attitude toward self medication. The study relied on a survey method using questionnaires to collect the required data. 438 questionnaires were obtained from patients who purchase non prescription drugs from Alexanandria Governorate. The study relied on a set of statistical methods, where descriptive analysis of the study variables was conducted by classifying the demographic characteristics of the sample units, as well as the mean and standard deviation for all study variables. Structural Equation Modeling was also relied upon to test the study hypotheses and ensure the presence of direct and indirect effect between the study variables. The study found a positive effect of marketing factors and personal factors on the purchase decision of non prescription drugs, and no effect of demographic factors on purchase decision of non prescription drugs. The study also found a mediating effect of non prescription drugs patients’ perception between both, marketing factors, personal factors, and non prescription drugs purchase decision.